2015
DOI: 10.1037/adb0000062
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gambling advertising: Problem gamblers report stronger impacts on involvement, knowledge, and awareness than recreational gamblers.

Abstract: Although there is a general lack of empirical evidence that advertising influences gambling participation, the regulation of gambling advertising is hotly debated among academic researchers, treatment specialists, lobby groups, regulators, and policy makers. This study contributes to the ongoing debate by investigating perceived impacts of gambling advertising in a sample of gamblers drawn from the general population in Norway (n = 6,034). Three dimensions of advertising impacts were identified, representing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 32 publications
9
64
1
6
Order By: Relevance
“…Our data support the inclusion of an “illusory control” variable in systems currently in development for gauging the likely public harms of any specific (e.g., new) form of gambling (e.g., Meyer, Fiebig, Häfeli, & Mörsen, 2011). Finally, our observed association between gambling-related illusory control and the Contingency Judgment task may be useful for gambling researchers, as a means of assessing control perceptions with a task that does not involve direct gambling cues, which can induce cravings and relapse in treatment-seeking individuals (Hanss, Mentzoni, Griffiths, & Pallesen, 2015). …”
Section: Discussionmentioning
confidence: 96%
“…Our data support the inclusion of an “illusory control” variable in systems currently in development for gauging the likely public harms of any specific (e.g., new) form of gambling (e.g., Meyer, Fiebig, Häfeli, & Mörsen, 2011). Finally, our observed association between gambling-related illusory control and the Contingency Judgment task may be useful for gambling researchers, as a means of assessing control perceptions with a task that does not involve direct gambling cues, which can induce cravings and relapse in treatment-seeking individuals (Hanss, Mentzoni, Griffiths, & Pallesen, 2015). …”
Section: Discussionmentioning
confidence: 96%
“…Participants in a study with a nationally representative sample of over 6,000 Norwegians gamblers reported that gambling advertising increased their knowledge of gambling brands, but did not have an impact on their gambling attitudes, interests, or behaviours. However, among problem gamblers, the same study noted that, after controlling for frequency of gambling advertising exposure, problem gamblers still experienced more advertisingderived impact than regular gamblers (Hanss et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 92%
“…Amongst the most prominent risk factors that these regulatory proposals emphasise is the vulnerability to gambling advertising of those already experiencing gambling disorder. Evidence from multiple jurisdictions has shown that excessive gamblers report higher levels of distress due to gambling advertising exposure, despite their perception that advertisements do not impact their gambling behaviour (Hanss, Mentzoni, Griffiths, & Pallesen, 2015;Hing, Lamont, Vitartas, & Fink, 2015), something also reported among adolescents (Derevensky et al, 2007). These studies typically rely on surveybased approaches with occasional and regular gamblers, while others recruit frequent gamblers for more in-depth qualitative studies (Thomas, Lewis, McLeod, & Haycock, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In order to quantify the influence of gambling marketing, several studies have sought to explore what association (if any) there is between awareness of, and participation with, gambling marketing and problematic gambling. A Norwegian study showed that problem gamblers were more likely to be aware of gambling marketing and to report that it increased their involvement in gambling [48]. Australian sports bettors, and in particular problem gamblers, who report taking advantage of advertised financial incentives appear to place more impulsive bets [49].…”
Section: Gambling Marketing's Effect On Behaviourmentioning
confidence: 99%